Bayesian Modeling Immune Reconstitution Apply to CD34+ Selected Stem Cell Transplantation for Severe Combined Immunodeficiency - Diana, Jean-Sebastien; Bouazza, Naïm; Couzin, Chloe; Castelle, Martin; Magnani, Alessandra; Magrin, Elisa; Rosain, Jeremie; Treluyer, Jean-Marc; Picard, Capucine; Moshous, Despina; Blanche, Stéphane; Neven, Bénédicte; et al. (Frontiers in Pediatrics, 2022)
Severe combined immunodeficiencies SCIDs) correspond to the most severe form of primary immunodeficiency. Allogeneic Hematopoietic Stem Cell Transplantation (HSCT) and Gene Therapy are curative treatments depending on the donor's availability and molecular diagnostics. A partially HLA-compatible donor used has been developed for this specific HSCT indication in the absence of a matched donor. However, CD34+ selected process induces prolonged post-transplant T cell immunodeficiency. The aim here was to investigate a modeling approach to predict the time course and the extent of CD4+ T-cell immune reconstitution after CD34+ selected transplantation. We performed a Bayesian approach based on age-related changes in thymic output and cell proliferation/loss model. For that purpose, we defined specific individual covariates from data collected for ten years of clinical practice and then evaluated the model's predicted performances and accuracy. We have shown that this Bayesian modeling approach predicted the time course and the extent of CD4+ T-cell immune reconstitution after SCID transplantation.